2014
DOI: 10.1111/ssqu.12106
|View full text |Cite
|
Sign up to set email alerts
|

Direct Democracy and Political Equality in the American States*

Abstract: Objectives. This study investigates the relationship between direct democracy and the equality of opinion-policy representation in the American states. Methods. Using public opinion measures from the National Annenberg Election Surveys and data on state policy outputs, I generate an index of the equality of political representation (based on citizens' incomes) that is comparable across the states. I then evaluate the relationship between different measures of direct democracy and political equality. Results. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Initiative elections provide a particularly important context in which to study cross-level deliberation. In spite of their broad popularity (Collingwood, 2012), initiative elections have received mixed reviews for their fidelity with public preferences (Flavin, 2015;Matsusaka, 2008;Nai, 2015) and their implications for minorities, in particular (Hajnal, Gerber, & Louch, 2002;Lewis, 2011;Moore & Ravishankar, 2012). There is also reason to be concerned about the quality of information on which voters judge such laws (Broder, 2000;Gastil, Reedy, & Wells, 2007;Milic, 2015;Reedy, Wells, & Gastil, 2014;Saris & Sniderman, 2004).…”
Section: Deliberative Designs and Direct Democracymentioning
confidence: 99%
“…Initiative elections provide a particularly important context in which to study cross-level deliberation. In spite of their broad popularity (Collingwood, 2012), initiative elections have received mixed reviews for their fidelity with public preferences (Flavin, 2015;Matsusaka, 2008;Nai, 2015) and their implications for minorities, in particular (Hajnal, Gerber, & Louch, 2002;Lewis, 2011;Moore & Ravishankar, 2012). There is also reason to be concerned about the quality of information on which voters judge such laws (Broder, 2000;Gastil, Reedy, & Wells, 2007;Milic, 2015;Reedy, Wells, & Gastil, 2014;Saris & Sniderman, 2004).…”
Section: Deliberative Designs and Direct Democracymentioning
confidence: 99%
“…This methodological approach could also be used in longitudinal analyses to investigate how the extent of unequal influence may vary over time, and whether political and macroeconomic conditions help explain this variation. Investigating the conditions under which middle‐ or low‐income Americans do wield a degree of political influence in particular states (see Flavin, 2014, 2015a, 2015b; Rigby and Wright, 2011, 2013) is also a fertile area for future research.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have found that federal representatives’ voting behavior is more closely related to the ideological preferences of the affluent than to those of the less affluent (e.g., Hayes, 2013). Additional evidence of unequal democracy based on constituents’ ideological preferences has been found in state legislatures (Flavin, 2012b, 2014, 2015a, 2015b; Rigby and Wright, 2011) and state party platforms (Rigby and Wright, 2013).…”
Section: The Unequal Responsiveness Debatementioning
confidence: 97%
See 1 more Smart Citation